PEER EDUCATION MODEL FOR FAMILY LIFE PREPARATION IN FEMALE ADOLESCENTS OF ISLAMIC BOARDING SCHOOLS (Proceedings of the Global Public Health Conference, 2025)
The high rate of early marriage in Indonesia is linear with the number of early marriages that occur among female adolescent in Islamic Boarding Schools (IBS). Several studies have shown that female adolescent do not yet have a good family life plan (do not know the safe age to marry, plan to have many children, do not know the safe pregnancy spacing and do not plan to use contraception). The purpose of this study was to develop peer education model in the intention of preparing family life for female adolescent in IBS (age of first marriage, number of children, pregnancy spacing and family planning). The study was conducted using quasi eksperimen pre-post test with control group design. The study was conducted in traditional IBS in EastJava Province, Indonesia. The research period was December 2022 to October 2023. The research sample was female adolescent aged 15-24 years, have been boarding for more than one year, in good health and have never participated in reproductive health education programs and preparation for family life during at IBS. The total sample is 204 with 51 respondents per group. There are three intervention groups (conventional, peer education of young ustadzah, peer education of fellow dormitories). Data analysis was carried out using the Generalized Linear Model Repeated Measure statistical test. The results of the study show that peer education has an effect in increasing the intention of preparing for family life of female adolescent in traditional IBS. Peer education of fellow dormitories has the most effect on increasing intention, especially in the 2nd and 3rd month measurements. Statistically showed no difference between young ustadzah and fellow dormitories peer education. So that pesantren administrators need to involve peers in program implementation to maximize the expected results.
Keywords: peer education; intention; preparation for family life; female adolescent; Islamic boarding school; quasi-experimentals